Surviving the crisis: Foreign multinationals vs domestic firms - Olivier Godart; Holger Görg; Aoife Hanley (Kiel Institute for the World Economy (IfW), 2011)
Starting from the observation that all firms in Ireland (foreign and domestic in manufacturing and services industries) were hit by the crisis, the paper asks whether there is a difference in the behaviour of foreign and domestic firms. One hypothesis is that foreign multinationals are less linked into the Irish economy, so more likely to leave once the economy is hit by a negative shock. The paper discusses background hypotheses before giving empirical evidence from firstly aggregate data, and secondly firm-level observations. The analysis of the latter suggests that foreign firms are not more likely to leave during the crisis than Irish firms. Some policy conclusions are offered in the paper.
Keywords: F23; 330; Firm survival; financial crisis; Ireland; Wirtschaftskrise; Finanzmarktkrise; Konkurs; Liquidation; Multinationales Unternehmen; Unternehmensentwicklung; Irland